Validation of body condition score system in Holstein x Zebu cows via ultrasound method during the transition period and early lactation - Narjara Rodrigues Gentil (Semina: Ciências Agrárias, 2017)
This study aims to validate, by means of subcutaneous rump fat thickness (RFT), the suitability of the visual evaluation of body condition score (BCS) to indicate the body condition of crossbred dairy cows (Holstein x Zebu) during the transition period and early lactation. Animals were selected according to lactation period and distributed into three groups: PP (0 to 4 weeks antepartum; n = 30), L4 (0 to 4 weeks postpartum; n = 15), and L + 5 (5 to 14 weeks postpartum; n = 63). The relationship among RFT, BCS, and body weight (BW) was investigated using correlation and regression analyses. The variables BCS, RFT, and BW were different among the three groups (P < 0.05). The correlations between BCS and RFT were higher in groups PP and L + 5 (r = 0.78 and r = 0.71 respectively). However, the L4 group showed a weak correlation (r = -0.04). The regression models were able to explain how much RFT varies because of changes in BCS, with coefficients of determination equal to 0.61 for PP and 0.51 for L + 5 group. In conclusion, BCS can be considered a good predictor of RFT for crossbred Holstein x Zebu cows in antepartum and postpartum for over 5 weeks of lactation.